ANALISIS INFORMASI AKUNTANSI DIFERENSIAL DALAM MEMBANTU PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA PERUSAHAAN INDAH CEMERLANG MALANG - Udiananta Genta Fitrio (Universitas Katolik Widya Karya Malang, 2019)
This study aims to determine the analysis of differentialaccounting information in assisting decision-making accept orreject special orders at Indah Indah Cemerlang Malang. Theproblem is that the company in decision-making is based onthe total costing, so that for special orders below the normalselling price is not accepted because it is considered not toprovide additional profits for the company.The results of the analysis with quantitative descriptivemethod that (1) Capacity of the company is not enough enoughto receive special order terrazzo tile size 30 x 30 cm in theyear 2014 as much as 2,875 m2, (2) There has been a marketseparation between regular sales with sales to serve specialorders whose price (3) Analysis of differential accountinginformation as the basis of decision making emphasize thetechnique of calculation by the method of variablecostingmaka company can maximize the profitability in 2014,where the calculation of profit / loss of the company for tegelterrazzo product size 30 x 30 cm Year 2014 is Rp.30.294.066,59, - obtained from the regular sale of Rp.21.693.872,00, - and additional profit from receiving specialorder Griya Singosari Inside Rp. 8,600,194,59, -. If thecompany receives a special order from Griya Tanjung PriokJaya, Grand Villa Dau, Dieng Inside and Bumi Royal Park thecompany should be able to earn additional profit of Rp.24,799,830.90, - so the calculation of profit / loss of thecompany for tegel teraso product size 30 x 30 cm can achieve amaximum profit of Rp. 55.093.896, 49, -.